The inclusion program at São Paulo state university: values, contradictions and affirmative action - Mário Sérgio Vasconcelos; Eduardo Galhardo (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This article has a wider aim to make a reflection about the process of affirmative policies implantation at University Teaching. More specifically, it aims to describe and done some notes about the Inclusion Project developed by Paulista State University (UNESP), since 2014, using the System of Vacancies Reservation of Public Basic Education. With this perspective, we introduce datas about the inclusive process, the profile of students and actions which are focused to students' permanency that support the inclusion at UNESP. At Least, we shows a sketch of an in progress research which has the objective to understand and evaluate the impacts and consequences of this inclusion process. The previews reflections performed allow to point some positive results and indicate that there are required integrated institutional actions to keep a worthy inclusive policy which are befitting with the quality principles that should guide the services at a public university.